EKSISTENSI ADAT MELAYU DALAM PENYELESAIAN KECELAKAAN LALU LINTAS DI KABUPATEN PELALAWAN - IKA ANGGITA; Erdianto Erdianto; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The united republic of Indonesia is a legal state with basis and guidelines to pancasila and the constitution of 1945 and the supreme rule of national law. Whereas national law is also growing and growing a legal system emanating form the customs of society called the tribal laws. The settlement using the customary law was done as an alternative to the smooth distribution of a misdemeanor. When a case is settled by the customary law it is possible for the public to use valid tribal sanction in order to prevent a pending trial. As a result of the law that would result in a criminal traffic accident in the juvenile district in fines and a civil ceremony of praying together.The solution using traditional sanction in the village of betung was effective so that there would be no grudge between the troubled. In study aims to see that tribal laws still exist and are still used in society. The customary law was still accepted by the indigenous people and made the customary sanction a legal basis for accomplishing a matter. According to the victims point of view, however the customary law of compliance with the victims losses would also be met and replaced by the perpetrators. So that the perpetrators can also be accepted by the public for replacing and delibering with victims witnessed by the indigenous population.The decision decided by the mind of Malay law is mandatory for both parties to accept the decision together. The decision is preceded by a customary agreement and according to the purpose of rehabilitate the perpetrator and restore balance in the lives of relative.Keywords: Customary law-Customary Sanction-Traffic accidents